In-situ EBSD investigation of orientation induced mechanical anisotropy in selective laser melted Al-Mn-Sc alloy - Wei Jiang; Yunlai Deng; Qingsong Dai; Xiaobin Guo (Materials Research Letters, 2023)
The mechanical anisotropy of selective laser melted (SLM) aluminum alloys resulting from heterogeneous grain structures is still not fully understood due to lacking study of grain orientation related mechanical response. Here, by introducing in-situ EBSD tensile method, the orientation induced anisotropy coefficient Ka related to the deformation-induced grain rotation was revealed by excluding effects of grain size and grain aspect ratio. Compared with traditional mechanical properties models by Taylor factor M, it was found that the orientation <001 > in as-built and <102 > in heat treatment contributed the most yield strength anisotropy, and introducing Ka predicts the mechanical anisotropy more accurately.